The association between salivary oxytocin, age, and puberty in children with and without OCD - Anna-Rosa Cecilie Mora-Jensen; Line Katrine Harder Clemmensen; Manja Gersholm Grønberg; Eli R. Lebowitz; Daniel S. Quintana; Niklas Rye Jørgensen; Charlotte Sewerin Larsen; Lasse Kristoffer Bak; Gitte Lund Christensen; Linea Pretzmann; Valdemar Uhre; Sofie Heidenheim Christensen; et al. (Scientific Reports)
Abstract The oxytocin system has been thought to contribute to obsessive-compulsive disorder (OCD). Few studies, only involving adults, have investigated this hypothesis and have found inconsistent results regarding oxytocin system activity and OCD. We investigated whether salivary oxytocin concentrations differed between children and adolescents with and without OCD and qualified our comparative analysis by investigating the possible covariates age, pubertal stage, and sex. Participants included 113 children and adolescents (8–17 years) with OCD and 88 children and adolescents without any previous or current psychiatric disorder and their parents (254 parents included). Salivary oxytocin concentrations were measured in children and parents with enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed using frequentist and Bayesian approaches. We found no evidence of a difference in mean salivary oxytocin concentrations between children and adolescents with and without OCD. Bayesian analysis indicated anecdotal to moderate support for the null hypothesis. We found an association between oxytocin and age and between oxytocin and pubertal stage, which by visual inspection of plots and post-hoc tests indicated nonlinear relationships. We found no association between oxytocin concentration and sex. Our findings do not suggest elevated oxytocin concentrations in pediatric OCD. Nonlinear changes in oxytocin across development show the importance of accounting for hormonal and behavioral changes during puberty.